Analysis of number of players involved in rebound situations in Euroleague basketball games - Ribas, R. L.; Navarro, R.; Tavares, F.; Gómez, M. A. (The Open Sports Sciences Journal, 2011)
The aim of the present study was to identify the influence of number of players involved in dispute of rebound in basketball games.To do so, 48 games corresponding to the 2009-2010 Top 16 of the Euroleague were analyzed. The sample was composed of 2170 situations (unsuccessful field-goals gathered which generate rebound), and the analyzed variables were: i)situations of equal number of 1, 2 and 3 players from offense and defense in rebound; ii) situations of superiority of 1, 2 and 3 players for defense; iii) situations of superiority of 1 player for offense; iv) all situations of superiority and inferiority in offense and defensive rebounds. The results of the present study showed that: i) when the number of players is equal, defense had no statistically significant more rebounds than offense; ii) when defense had superiority of 1, 2 and 3 players, it had statistically significant more rebounds than offense; iii) when offense had superiority of 1 player, it had statistically significant more rebounds than defense; iv) situations of superiority had statistically significant more rebounds than inferiority. Coaches and researches should be aware of this kind of information to enhance practices and games performance.